2014
DOI: 10.1016/j.kjms.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the effectiveness of 99mTc‐dimercaptosuccinic acid scans for selective voiding cystourethrography in children with a first febrile urinary tract infection

Abstract: Recent studies have yielded conflicting results regarding the ability of technetium-99m dimercaptosuccinic acid ((99m)Tc-DMSA) renal scans for identifying high-grade vesicoureteral reflux (VUR) in children with a first febrile urinary tract infection (UTI). This study aimed to reevaluate the effectiveness of (99m)Tc-DMSA renal scans for selective voiding cystourethrography (VCUG) in children with a first febrile UTI. The medical records of children aged ≤ 5 years who were admitted with a first febrile UTI were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, in that study and other previous studies the decision was based on presence of scar in renal parenchyma. Several other studies have pointed out the same finding and have concluded that cystourethrography is indicated in only patients with DMSA abnormalities [2]. This methodology has high sensitivity and negative predictive value in the detection of high grade VUR (86% and 93% respectively) [2,3].…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, in that study and other previous studies the decision was based on presence of scar in renal parenchyma. Several other studies have pointed out the same finding and have concluded that cystourethrography is indicated in only patients with DMSA abnormalities [2]. This methodology has high sensitivity and negative predictive value in the detection of high grade VUR (86% and 93% respectively) [2,3].…”
Section: Introductionmentioning
confidence: 55%
“…Several other studies have pointed out the same finding and have concluded that cystourethrography is indicated in only patients with DMSA abnormalities [2]. This methodology has high sensitivity and negative predictive value in the detection of high grade VUR (86% and 93% respectively) [2,3]. The Visualization of the dilated collecting system in DMSA scintigraphy has never been analyzed previously.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation